A Textile Object in the Art of the 20th — 21st Centuries - Tsvetkova, Nataliia N. (Actual Problems of Theory and History of Art, 2018)
This article explores “textile sculpture” (“soft sculpture”) and attempts to situate it within art history continuum. The debate continues as to whether the three-dimensional works of textile art are merely decorative craft items or monumental works of art. Three-dimensional textile art works can be described as an “art object” according to the analysis of twentieth century articles on art and the study of contemporary authors. The three-dimensional “textile sculpture” in the 1960s contributed to the development of this form and to the emergence of ever larger forms. In the 1970s, the textile art objects became miniaturized. The term “fiber art” was coined in the second half of the 20th century. The analysis of contemporary textile art objects, using catalogues of textile art exhibitions in 2010-2016, indicates that this art form continues to evolve and remains popular. The works presented at textile art exhibitions provide the evidence of the significance given to conceptual thinking. The artists working with fiber address such relevant topics as human relationships, environmental and social issues among other topics and themes. This investigation concludes that we can undoubtedly consider fiber art as contemporary art.